Influence of Stem Cell Therapy on Thyroid Function and Reactive Oxygen Species Production in Diabetic Rats - da Silva, Diorney Luiz Souza Gran; de Freitas, Mariana Lopes; Cahil, Gustavo Monnerat; de São José, Vitória Santório; Neto, Felippe Mousovich; Cardoso, Ricardo Cortez; da Costa, Vânia Maria Correa; Fortunato, Rodrigo Soares; de Carvalho, Denise Pires; Medei, Emiliano Horácio; Ferreira, Andrea Claudia Freitas (Hormone and Metabolic Research, 2018)
Cell therapy with mesenchymal stem cells (MSC) has been proposed for the treatment of diabetes mellitus (DM). It is known that the prevalence of thyroid disease is higher among diabetic patients than in general population. Therefore, our aim was to investigate the effect of the treatment with MSC on thyroid function and ROS generation in an experimental model of type 1 DM. Adult male Wistar rats were divided into the following groups: control, DM (80 mg/kg BW streptozotocin, iv.) and DM+MSC. MSC treatment occurred 4 weeks after DM induction and the animals were euthanized 4 weeks after MSC administration. We also evaluated the effect of co-culture with MSC or extracellular vesicles (EV) obtained from these cells on the rat thyroid cell line PCCL3 exposed to high glucose. Thyroid H2O2 generation was increased in DM, which was reversed by MSC treatment. These changes paralled a significant DuOx1 mRNA increase. The incubation of PCCL3 with high glucose increased extracellular H2O2 generation, which was reversed by both the co-culture with MSC and EV. Even though MSC treatment normalized thyroid ROS generation, serum thyroid hormone (TH) concentration remained low, along with increased serum TSH concentrations. Thyroperoxidase (TPO) activity, was reduced in DM, and MSC treatment did not normalize TPO. Therefore, we conclude that the treatment with MSC was able to reverse the increased thyroid H2O2 generation in diabetic animals and in PCCL3 cells exposed to high glucose, an effect probably mediated by EV produced by these cells, acting in a paracrine fashion.
Keywords: reactive oxygen species; thyroperoxidase; mesenchymal stem cells; diabetes mellitus